A Priori Estimates and Existence of Positive Solutions to Quasilinear Elliptic Equations in General Form (Journal of Partial Differential Equations, 2020)
In this paper we prove the existence of a positive solution to the following superlinear elliptic Dirichlet problem, - &#931^n_{i,j=1}aij(x, u, Du)D_{ij}u = f(x, u, Du) in &#937, \quad u = 0 on &#8706&#937 where f satisfies certain growth conditions.
Keywords: Elliptic equation; positive solution